Designing safety interventions for specific contexts: results from a literature review - Karanikas, Nektarios; Khan, Shanchita R.; Baker, Philip R. A.; Pilbeam, Colin (Elsevier, 2022)
A misalignment between safety interventions and the workplace context of their application could lead to diminished effectiveness or failure. This paper is the first of three of an umbrella study that aimed to understand whether and how researchers and organisations consider contextual factors in safety interventions. Through Rapid Evidence Assessment (REA) process, we searched and selected scholarly work indexed in the bibliographic databases Medline, APA PsycArticles, Web of Science and Scopus between January 2011 and June 2021. The studies were analysed using a framework developed according to translation theory about (de)contextualisation of knowledge. The framework was enriched to consider psychosocial factors at the organisational level and physical, cognitive and emotional factors of the interventions’ recipients. We identified 73 eligible studies, of which 47 described safety interventions that had not been deployed in workplaces (e.g., pilot studies and concepts) and 26 studies referred to those deployed. No study considered all factors of the framework. Communication and support from management and colleagues were the most considered psychosocial factors, whereas conflicting demands and job security were the least considered. Moreover, cognitive factors of workers were mentioned in 77% of the sample, with only one study considering inclusively cognitive, emotional and physical factors of recipients. About 62% of the implemented interventions were functional (e.g., training, education and communication-related interventions), with only four studies reporting physical interventions. Also, most of the interventions were sourced from the literature and introduced as ‘new practice’ at the targeted workplaces, with only one article reporting a failed intervention. Overall, the findings of this research indicated that intervention studies did not visibly follow a translation-transformation path between sources and recipients, did not systematically consider contextual factors at the workplaces targeted, and all interventions represented administrative controls, contrary to the widely accepted principle of the hierarchy of controls.
Keywords: Occupational safety; Safety interventions; workplace context; psychosocial factors